(3cJGH aj CMGOjK GdNdGas
(3ChdgG (B:s
(3JHJOF HMOjK BNQ ef GdefShN , MOKfG TYjH Hf eMeO GdPGQY EedGA jhe GdLeYI SfI KeGf hKdGK eGFI ffG eMeO Hf CHj eYTQ Gdhjfi s
(3BNQgG (B:s
(3GdNdGa ai Pdc MOKfG CHh HcQ GdfjSGHhQi bGd MOKfi YjSi Hf CHj YeQGf HGdQedI ced GdcJGH HMeO Gddg hMSf Yhfg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs